Hospital Readmissions Reduction Program: An Economic and Operational Analysis - Zhang, Dennis J.; Gurvich, Itai; Van Mieghem, Jan A.; Park, Eric; Young, Robert S.; Williams, Mark V. (Management Science, 2016)
The Hospital Readmissions Reduction Program (HRRP), a part of the U.S. Patient Protection and Affordable Care Act, requires the Centers for Medicare and Medicaid Services to penalize hospitals with excess readmissions. We take an economic and operational (patient flow) perspective to analyze the effectiveness of this policy in encouraging hospitals to reduce readmissions. We develop a game-theoretic model that captures the competition among hospitals inherent in HRRP’s benchmarking mechanism. We show that this competition can be counterproductive: it increases the number of nonincentivized hospitals, which prefer paying penalties over reducing readmissions in any equilibrium. We calibrate our model with a data set of more than 3,000 hospitals in the United States and show that under the current policy, and for a large set of parameters, 4%–13% of the hospitals remain nonincentivized to reduce readmissions. We also validate our model against the actual performance of hospitals in the three years since the introduction of the policy. We draw several policy recommendations to improve this policy’s outcome. For example, localizing the benchmarking process—comparing hospitals against similar peers—improves the performance of the policy. This paper was accepted by Serguei Netessine, operations management.